2016
DOI: 10.1080/09638288.2016.1239768
|View full text |Cite
|
Sign up to set email alerts
|

Addressing challenges for youths with mobility devices in winter conditions

Abstract: Therapists/clinicians and designers should address winter-related accessibility problems in areas with abundant snow. Implications for Rehabilitation Several studies show that current urban contexts do not necessarily respond accurately to the needs of individuals with limited mobility. Winter-related research about the experience of navigating in the urban context is limited and has mostly focused on the elderly population with physical disabilities. Our results clearly show that youth who use mobility device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“… 45 , 51 The remaining six studies designed interventions for CYP only. 46 , 47 , 48 , 49 , 50 , 53 There was no noticeable difference between the intervention function types used when both CYP and parents were engaged compared to when only CYP were engaged (Table 4 ). However, the training intervention function type was only used with interventions designed to target CYP.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“… 45 , 51 The remaining six studies designed interventions for CYP only. 46 , 47 , 48 , 49 , 50 , 53 There was no noticeable difference between the intervention function types used when both CYP and parents were engaged compared to when only CYP were engaged (Table 4 ). However, the training intervention function type was only used with interventions designed to target CYP.…”
Section: Resultsmentioning
confidence: 97%
“…45,51 The remaining six studies designed interventions for CYP only. [46][47][48][49][50]53 There was no noticeable difference between the intervention function types used when both CYP and parents were engaged compared to when only CYP were engaged (Table 4).…”
Section: Target and Types Of Interventionsmentioning
confidence: 99%
“…A recent study found that it would be feasible to create traction devices for wheelchairs in the winter to improve slip resistance and steerability. 17 Currently, winter tires are not readily available for mobility scooters. With customized solid 254 mm (10 in) diameter prototype winter tires, the two scooters that we tested had an improved upslope and downslope performance of 18.6% and 33.4%, respectively, compared to stock tires.…”
Section: Winter Tire Performancementioning
confidence: 99%
“…Winter conditions can present serious obstacles for individuals living with a wide range of disabilities (snow and ice made walking dangerous, tires and casters becoming stuck in the snow, difficulty ascending inclines or ramps, and cold hands while using controls or pushing rims, frozen batteries, seat cushions or backrests, or electronics) [2][3][4][5][6]. Having initiated our research activities, we have identified some challenges in carrying out interviews with certain disability groups during winter weather conditions.…”
Section: Introductionmentioning
confidence: 99%